Pharmacognostic Evaluation and Phytochemical Investigation of Stem Bark of Nothopegia Racemosa (Dalz) - C.H, Poornima.; Shastri, Rajesh; Habbu, Prasanna; Hiremath, G.S.; Y. Srinivas, Y. Srinivas (Journal of Neonatal Surgery, 2025)
Nothopegia racemosa (Dalz). (Anacardieae) a Small trees, up to 7 m tall, generally found in Karnataka and other tropical regions. Traditionally the plant fruits are used to prepare pickles. Scientifically the plant possesses hepatoprotective, antioxidant, and lipid lowering activity. In the present study systematic Pharmacognostic work this includes Organoleptic, Macroscopy, Microscopy and Phytochemical screening was carried out. Methods: The stem bark of plant Nothopegia racemosa. Dalz. Were collected from Dandeli, Tinaighat , Malsang forest area Karnataka and authenticated by Taxonomist. Washed stem bark were Shade dried and powdered to courser size and store in air tight container. Organoleptic, macroscopic and microscopic characters were studied. Extractive values, moisture content and ash values were carried out, with powdered crude drug were subjected to successive soxhlet extraction with Pet ether, Ethyl acetate, Ethanol and Aqueous extraction. Phytochemical screening of all these extracts were carried out. Results: Microscopically the TS of leaves and stem bark show the presence of stomata, xylem vessels, ca-oxalate crystals, cork, cortex, phloem, pith etc. These diagnostic features of the plant will help in the identification and authentification process of the drug. Preliminary Phytochemical Investigation of the successive extract of the stem bark revealed the presence of tannins, Polyphinolic compounds, steroids, flavonoids, glycosides. Conclusion:The present study enabled us to set up the parameters for standardization of the drug. The results of the investigations justify the folklore use of Nothopegia racemosa (Dalz).in the treatment of diseases of head, kideny and lever. The plant is worth for further chemical and pharmacological investigations.